Cancer Morbidity of Foundry Workers in Korea - Ahn, Yeon-Soon (The Korean Academy of Medical Sciences, 2010)
Foundry workers are potentially exposed to a number of carcinogens. This study was conducted to describe the cancer incidence associated with employment in small-sized Korean iron foundries and to compare those findings to the Korean population. Cancer morbidity in 208 Korean foundries was analyzed using the Standardized Incidence Ratio (SIR) and Standardized Rate Ratio (SRR). Overall cancer morbidity in foundry workers (SIR=1.11, 95% confidence interval [CI]=1.01-1.21) was significantly higher than that of Korean general population. Lung cancer (SIR=1.45, 95%CI=1.11-1.87) and lymphohematopoietcic cancer (SIR=1.58, 95%CI=1.00-2.37) in production workers were significantly high compared to Korean general population. Stomach cancer in fettling (SRR=2.10, 95%CI=1.10-4.01) and lung cancer in molding (SRR=3.06, 95%CI=1.22-7.64) and in fettling (SRR=2.63, 95%CI=1.01-6.84) were there significant elevations compared to office workers. In this study, statistically significant excess lung cancer was observed in production workers comparing to Korean general population and office workers. Also, cancer morbidity of overall cancer, lung cancer and stomach cancer was significantly increased with duration of employment at ten and more years comparing to Korean general population. These findings suggest in causal association between exposure to carcinogens during foundry work and cancer morbidity.